Popcorn days & buttermilk nights - Paulsen, Gary (Puffin Books, 1989)
Carley recalls the extraordinary summer when, as a troubled fourteen-year-old, he first came to northern Minnesota to stay with his blacksmith Uncle David and gained not only new skills but also a new sense of himself.